2019
DOI: 10.1021/acsphotonics.9b00452
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopically Aligned Carbon Nanotubes as a Refractory Platform for Hyperbolic Thermal Emitters

Abstract: Refractory nanophotonics, or nanophotonics at high temperatures, can revolutionize many applications, including data storage and waste heat recovery. In particular, nanophotonic devices made from hyperbolic materials are promising due to their nearly infinite photonic density of states (PDOS). However, it is challenging to achieve a prominent PDOS in existing refractory hyperbolic materials, especially in a broad spectral range. Here, we demonstrate that macroscopic films and architectures of aligned carbon na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
1
38
1
2
Order By: Relevance
“…That nanotube films could function as hyperbolic metamaterials is intuitive: along the nanotube alignment direction, free charges can oscillate freely (a metal-like optical permittivity), whereas perpendicular to the film, free charge conductivity is relatively suppressed (leading to a dielectric-like permittivity). Recently, this property been experimentally verified: by using ellipsometry [33] and reflectometry, [34] two separate studies found hyperbolic dispersion in aligned nanotube films One of the unique functionalities of nanotube hyperbolic metamaterials is that their optical properties are a strong function of carrier concentration-thus they function as tunable hyperbolic metamaterials. This functionality is virtually nonexistent in natural crystals and extremely rare even in engineered hyperbolic metamaterials.…”
Section: (3 Of 5)mentioning
confidence: 90%
See 1 more Smart Citation
“…That nanotube films could function as hyperbolic metamaterials is intuitive: along the nanotube alignment direction, free charges can oscillate freely (a metal-like optical permittivity), whereas perpendicular to the film, free charge conductivity is relatively suppressed (leading to a dielectric-like permittivity). Recently, this property been experimentally verified: by using ellipsometry [33] and reflectometry, [34] two separate studies found hyperbolic dispersion in aligned nanotube films One of the unique functionalities of nanotube hyperbolic metamaterials is that their optical properties are a strong function of carrier concentration-thus they function as tunable hyperbolic metamaterials. This functionality is virtually nonexistent in natural crystals and extremely rare even in engineered hyperbolic metamaterials.…”
Section: (3 Of 5)mentioning
confidence: 90%
“…That nanotube films could function as hyperbolic metamaterials is intuitive: along the nanotube alignment direction, free charges can oscillate freely (a metal‐like optical permittivity), whereas perpendicular to the film, free charge conductivity is relatively suppressed (leading to a dielectric‐like permittivity). Recently, this property been experimentally verified: by using ellipsometry [ 33 ] and reflectometry, [ 34 ] two separate studies found hyperbolic dispersion in aligned nanotube films…”
Section: Emergent Optical Properties Of Nanotube Assembliesmentioning
confidence: 94%
“…Egy új német tanulmány szerint a szélerőművek -megfelelő támogatási politika esetén -elvileg egész Európa ellátását megoldhatnák (Rydberg et al, 2019). A fotovoltaikus energia-előállításban is vannak arra mutató jelek, hogy a jelenlegi 22-36%-os energiaátalakítási hatékonyság a Rice University újabb szén nanocsöves kutatási eredményei szerint (Gao et al, 2019) az infravörös hányadnak a látható fotonspektrumba konvertálásával elvileg akár 80%-ra is emelhető. A 3. ábrán szembetűnő, hogy ma az azonos energiamennyiség előállítására képes energiaforrások létesítésének fajlagos anyagigénye (t/TWh) a hagyományos (cement, beton, acél, üveg és egyéb) anyagokból milyen óriási eltérést mutat!…”
Section: A Megújuló Energiaforrások Nyersanyagháttereunclassified
“…Csakhogy, mint láttuk, a voksok megszerzéséért folytatott versenyben a rendkívül komplex globális ökoszisztéma egy-egy elemének tudományosan megalapozatlan, "kampányszerű" fejlesztésével a környezetben is nagyobb kárt okozhatunk, mint a kezelni kívánt probléma maga. Az üdvözlendő napenergia-hasznosító nanotechnológiai fejlesztések mellett (Gao et al, 2019) a technológiai lehetőségek mindenhatóságának túlhangsúlyozása a káros folyamatok megfékezésében, például nanorendszerek fejlesztése a légköri CO 2 -koncentráció globális megkötésére (Han-Zhien, 2019), sokszor a legkézenfekvőbb természetes megoldásokat szorítja háttérbe.…”
Section: öSszefoglalásunclassified
“…hyperbolic resonances across this wavelength range could be combined with the unique functional capabilities of nanotubes for new applications. The temperature stability and low thermal mass of carbon nanotubes could be combined with resonant spectral selectivity at multiple frequencies to enable thermal emitters with tailored spectral properties [20,[34][35][36][37][38]. Nanotubes supporting multiple resonances could be used for multiband surface-enhanced infrared absorption (SEIRA) with actively tunable resonant frequencies [39,40].…”
mentioning
confidence: 99%